The impact of an enhanced recovery programme on length of stay and post-discharge resource usage following hip and knee arthroplasty: a service evaluation and cost analysis - David J. Milligan (The British Editorial Society of Bone & Joint Surgery, 2021)
Aims: The aim of this study is to assess the impact of a pilot enhanced recovery after surgery (ERAS) programme on length of stay (LOS) and post-discharge resource usage via service evaluation and cost analysis. Methods: Between May and December 2019, 100 patients requiring hip or knee arthroplasty were enrolled with the intention that each would have a preadmission discharge plan, a preoperative education class with nominated helper, a day of surgery admission and mobilization, a day one discharge, and access to a 24/7 dedicated helpline. Each was matched with a patient under the pre-existing pathway from the previous year. Results: Mean LOS for ERAS patients was 1.59 days (95% confidence interval (CI) 1.14 to 2.04), significantly less than that of the matched cohort (3.01 days; 95% CI 2.56 to 3.46). There were no significant differences in readmission rates for ERAS patients at both 30 and 90 days (six vs four readmissions at 30 days, and nine vs four at 90 days). Despite matching, there were significantly more American Society of Anesthesiologists (ASA) grade 3 patients in the ERAS cohort. There was a mean cost saving of £757.26 (95% CI £-1,200.96 to £-313.56) per patient. This is despite small increases in postoperative resource usage in the ERAS patients. Conclusion: ERAS represents a safe and effective means of reducing LOS in primary joint arthroplasty patients. Implementation of ERAS principles has potential financial savings and could increase patient throughput without compromising care. In elective care, a preadmission discharge plan is key. Cite this article: Bone Jt Open 2021;2(11):966–973.